Объяснение:
[tex]1.3 - 3.6 \times (x - 3) = 5 \times (8 - 0.4x)[/tex]
[tex]1.3 - 3.6x + 10.8 = 40 - 2x[/tex]
[tex]12.1 - 3.6x = 40 - 2x[/tex]
[tex] - 3.6x + 2x = 40 - 12.1[/tex]
[tex] - 1.6x = 27.9[/tex]
[tex]x = - 17.4375[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Объяснение:
[tex]1.3 - 3.6 \times (x - 3) = 5 \times (8 - 0.4x)[/tex]
[tex]1.3 - 3.6x + 10.8 = 40 - 2x[/tex]
[tex]12.1 - 3.6x = 40 - 2x[/tex]
[tex] - 3.6x + 2x = 40 - 12.1[/tex]
[tex] - 1.6x = 27.9[/tex]
[tex]x = - 17.4375[/tex]